The Influence of the Implementation of Value Education, Religious Habituation, and Students’ Moral Intelligence at MA Miftahul Ulum Tempuran, Bantaran, Probolinggo - Martatik; Ahmad Hisyam As Sibli; MiftahurRisqi Sirat; Muhammad Alfi Syahrin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aims to analyze the influence of value education implementation and religious habituation on students’ moral intelligence at MA Miftahul Ulum Tempuran Bantaran Probolinggo. The research employed a quantitative approach using a survey method. The population consisted of all students of MA Miftahul Ulum, while the sample was determined through purposive sampling techniques. Data collection techniques included questionnaires, observations, and documentation. The research instrument used a Likert scale that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of the Statistical Package for Social Science (SPSS) application. The results showed that the implementation of value education had a positive and significant effect on students’ moral intelligence. Religious habituation was also proven to have a positive and significant influence on students’ moral intelligence. Simultaneously, value education implementation and religious habituation contributed strongly to improving students’ moral intelligence. The findings indicate that value-based education and religious culture are effective in shaping students’ character to become more disciplined, responsible, honest, and socially aware. This study emphasizes the importance of strengthening character education and religious habituation in addressing moral challenges among young generations in the digital era. Therefore, schools are expected to continuously develop value education and religious culture programs to create students who excel academically and morally